Exploring itinerant states in divalent hexaborides using rare-earth L edge resonant inelastic x-ray scattering. (30th December 2019) - Sheets, Donal; Flynn, Vincent; Kim, Jungho; Upton, Mary; Casa, Diego; Gog, Thomas; Fisk, Zachary; Dzero, Maxim; Rosa, Priscila F S; Mazzone, Daniel G; Jarrige, Ignace; Zhu, Jian-Xin; et al.
Abstract: We present a study of resonant inelastic x-ray scattering (RIXS) spectra collected at the rare-earth L edges of divalent hexaborides YbB6 and EuB6 . In both systems, RIXS-active features are observed at two distinct resonances separated by eV in incident energy, with angle-dependence suggestive of distinct photon scattering processes. RIXS spectra collected at the divalent absorption peak resemble the unoccupied 5 d density of states calculated using density functional theory. We discuss possible origins of this correspondence including a scenario which changes the 4 f valence. In addition, anomalous resonant scattering is observed at higher incident energy, where no corresponding absorption feature is present. Our results demonstrate the potential for L -edge RIXS to assess the itinerant-state properties of f -electron materials.